THE MULTIDIMENSIONAL ROLE OF HEALTH TOURISM AS A PART OF THE GREEN ECONOMY IN THE FUNCTION OF SUSTAINABLE DEVELOPMENT OF THE REPUBLIC OF SERBIA : DOI: 10.5937/etp2402043A - Andjelković, Danijela; Vapa Tankosić, Jelena; Petrović, Vesna; Liberakos, Ana (Ekonomija - teorija i praksa, 2024)
Pronounced multidimensional effects of the development of health tourism are reflected through direct, indirect and induced impacts, namely on GDP, employment, investments, etc. The aforementioned multidimensionality stems from the fact that tourist consumption is a reflection of several interconnected activities that make up health tourism. Bearing in mind the cross-sectoral connection of various activities, the main purpose of this work is to study the basic determinants of ecological sustainability in health tourism and, on that basis, especially the impact of tourist consumption on the achievement of sustainable development goals in the Republic of Serbia. The intersectoral connection of various activities, especially emphasizes that tourism as part of the green economy is a necessary condition for sustainable development. The paper deals specifically with issues of product quality, that is, tourist services and, accordingly, how it affects consumers in health tourism. The interactive involvement of users of health tourism services gains new importance in destination strategies, focusing on the quality of the overall offer package. Moreover, creating experiences at the convergence of tourism production and tourism consumption is a very important topic in the function of health tourism development.